Eunug in die antieke Nabye Ooste - M. Nel (Acta Theologica)
The Bible uses the term “eunuch” several times. The question arises as to the meaning  of this term. In this article Biblical and extra-Biblical data are considered. It is argued that the Hebrew word, syrs, refers to a castrated man, and that, in biblical usage, it refers to a castrated man in terms of Israel’s religion (Deut. 23:1; Is. 56:3). The term is used in a different sense when it refers to a foreign person, i.e. a person in an official capacity in a king’s court (as in Gen. 37), or a military commander (as in 1 Kings 22:9; 2 Kings 8:7; 23:12; 25;19; Jer. 52:25). The reference to the Ethiopian eunuch in Acts 8 is also discussed, and the conclusion is drawn that syrs refers to a foreign official visiting Jerusalem to worship, and not to a castrated man.